Genomic analysis of antimicrobial resistant Escherichia coli isolated from manure and manured agricultural grasslands - C. Tyrrell; C. M. Burgess; F. P. Brennan; D. Münzenmaier; D. Drissner; R. J. Leigh; F. Walsh (npj Antimicrobials and Resistance)
Abstract Antimicrobial resistance (AMR) is a multifactorial issue involving an intertwining relationship between animals, humans and the environment. The environment can harbour Escherichia coli that are pathogenic or commensal. Escherichia coli is used as an indicator of environmental faecal contamination. Through culture dependent approaches this study identified 46 E. coli isolates in porcine and bovine manure, non-manured and manured soil, and manured grass. The grass isolation highlights grass as an environmental reservoir for E. coli. We also identified a diverse plasmidome with 23 different plasmid replicon types. The E. coli isolates were phenotypically antimicrobial resistant, predominantly multidrug resistant. Whole genome sequencing identified 31 antimicrobial resistance genes, and mutations in the gyrA, parC, and parE genes, conferring fluoroquinolone resistance. This study demonstrates grass as an understudied environmental niche of AMR E. coli, which directly links the environment to the grass grazing animal and vice-versa via the circular economy of manure application.